Factors influencing the length of the recovery period after blepharoplasty: a review of the latest data - Nieć, Maria; Olejarz, Zuzanna; Nowak, Karolina; Drygała, Zuzanna; Wyrwał, Julia; Zielińska, Zuzanna; Słowik, Magdalena; Nowak, Karolina; Gierlach, Katarzyna; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Blepharoplasty is a surgical procedure aimed at restoring the functionality and/or aesthetics of the eyelids. The aim of the study is to draw attention to the factors influencing the recovery period at successive stages of therapeutic procedures. A brief description of the state of knowledge: Preoperative consultation is important in selecting patients, planning surgical procedures, identifying potential complications and meeting patients’ expectations. In patients with hypertension, diabetes, smoking, and anticoagulant treatment, a worse scar assessment, longer recovery period and more complications have been observed. Patients who have undergone refractive surgery within the last 6 months are not suitable candidates for blepharoplasty. Nutrition status has a significant impact on wound healing and tissue repair after aesthetic medicine procedures. The use of continuous sutures compared to tissue glue results in similar wound healing time and postoperative discomfort level. Postoperative wound care is essential for the healing process. Electrostimulation of the wound does not accelerate edema reduction. We have focused on many complications, such as swelling, bleeding, infections, eyelid malposition, dry eye syndrome, wound dehiscence, ways to cope with these problems, and the role of lasers. Summary (conclusions): Important is the proper preparation of the patient for the procedure. A detailed interview and examination influence therapeutic decisions, allowing the doctor to choose the most optimal treatment methods that will shorten the recovery time. Blepharoplasty is one of the most commonly performed aesthetic procedures, so we propose the development of publicly accessible standards that should be included in the initial interview.